An Illustrated Treasury of Dragon Tales : Stories from Around the World - Breslin, Theresa; Leiper, Kate (Edinburgh : Floris Books, 2024)
Discover tales of dragons around the world, from Russian treasure hoarders to scaly Japanese princesses and winged Mexican gods, in this gorgeously illustrated gift anthology. From the acclaimed creators of the Illustrated Scottish Treasuries collection.
Keywords: Animals -- Fairy tales; Fairy tales